Narratives of Environmental Challenges in Brazil and India : Losing Nature. - Andrade, Ligia (Ecocritical theory and practice., 2018)
Narratives of Environmental Challenges in Brazil and India: Losing Nature is comprised of research on the representation and interrogation of environmental issues in both subcontinents, Brazil and India.